Understanding and Measuring Entrepreneurial Leadership Style. (29th December 2013) - Renko, Maija; El Tarabishy, Ayman; Carsrud, Alan L.; Brännback, Malin
<x xml:space="preserve">Abstract</x> Although entrepreneurial leadership is embraced in the popular press and in classrooms, academic knowledge remains underdeveloped. We develop the construct of entrepreneurial leadership and argue that it involves influencing and directing the performance of group members toward achieving those organizational goals that involve recognizing and exploiting entrepreneurial opportunities. We discuss environmental, organizational, and follower‐specific contingencies that may influence the success of entrepreneurial leadership, and we test the reliability and validity of an empirical measure for this construct (the ENTRELEAD scale). Using this novel measurement tool, we find that entrepreneurial leadership is more prevalent among founder‐leaders than nonfounder leaders, which indicates construct validity.